Turkmenistan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Turkmenistan during 1992-96. There was a general strengthening of centralized controls during 1993-95 to protect international reserves. Monetary and exchange rate policies were geared toward sustaining a network of implicit taxes and subsidies that helped promote selected areas of economic activity and provide social protection. Real GDP declined by nearly 19 percent in 1994, reflecting, for the most part, contraction of the gas and cotton sectors. Gas production declined continuously from 87.8 billion cubic meters in 1990 to 35.7 billion cubic meters in 1994.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet